The Effect of Adjunctive Mangosteen Pericarp on Cognition in People With Schizophrenia: Secondary Analysis of a Randomized Controlled Trial - Marx, Wolfgang; Skvarc, David R.; Mohebbi, Mohammadreza; Walker, Adam J.; Meehan, Alcy; Turner, Alyna; Baker, Andrea; Dodd, Seetal; Cotton, Sue M.; Scott, James Graham; Kavanagh, Bianca E.; Ashton, Melanie M.; et al. (Frontiers in Psychiatry, 2021)
Background: Cognitive impairment is prevalent and often highly burdensome in people with schizophrenia. The aim of this study was to investigate if mangosteen (Garcinia mangostana Linn.) pericarp extract may be an effective intervention to improve cognitive performance in this population. Methods: This was a secondary analysis of a larger randomized placebo-controlled trial that investigated a 24-week intervention of mangosteen pericarp extract supplementation in people diagnosed with schizophrenia. A subset of n=114 participants with completed cognitive outcomes at follow up were included in this analysis. Using the Cogstate Brief Battery, the following cognitive outcomes were assessed: psychomotor function, attention, visual learning and memory (visual and working). Subgroup analyses investigated whether baseline clinical parameters (baseline cognitive functioning, illness severity and duration, depressive symptoms) moderated the relationship between mangosteen pericarp extract intervention and change in cognitive outcomes. Results: There were no significant between-group changes in any cognitive outcomes assessed. Subgroup analysis based on baseline cognition and clinical characteristics did not reveal any significant between-group difference in change. Conclusions: Mangosteen pericarp extract did not affect cognitive outcomes in people with schizophrenia. Further investigation regarding optimal dosing strategies for mangosteen interventions and the testing of additional cognitive domains may be warranted.